Changes in the Budget Structure of Polish Households in the Years 2008–2018 - Socha, Paweł; Szynkaruk, Paulina (Journal of Finance and Financial Law, 2020)
In recent years, the economic situation in Poland has undergone dynamic changes. These changes had an impact on the standard of living of Poles, by affecting their financial situation. The article presents and analyzes the characteristics of changes in the structure of polish household budgets in 2008-2018. Issues such as income and expenditure, expenditure structure, tendency and dynamics of changes, including demographic and economic factors, has been discused in this article. In addition to analyzing the data on the structure of household budgets, the causes responsible for such and not other directions of changes has been also identified.